2013
DOI: 10.1155/2013/571420
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Spermatogenic Activity of the Root Extract of Ashwagandha (Withania somnifera) in Oligospermic Males: A Pilot Study

Abstract: Ashwagandha (Withania somnifera) has been described in traditional Indian Ayurvedic medicine as an aphrodisiac that can be used to treat male sexual dysfunction and infertility. This pilot study was conducted to evaluate the spermatogenic activity of Ashwagandha root extract in oligospermic patients. Forty-six male patients with oligospermia (sperm count < 20 million/mL semen) were enrolled and randomized either to treatment (n = 21) with a full-spectrum root extract of Ashwagandha (675 mg/d in three doses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 24 publications
6
71
0
4
Order By: Relevance
“…Furthermore, a significantly greater improvement and regulation were observed in serum hormone levels with the Ashwagandha treatment as compared to the placebo. (Vijay R. Ambiye et al 2013) [33]. Withania somnifera possesses phytoremedial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significantly greater improvement and regulation were observed in serum hormone levels with the Ashwagandha treatment as compared to the placebo. (Vijay R. Ambiye et al 2013) [33]. Withania somnifera possesses phytoremedial effect.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract of this herb has been shown to improve spermatogenesis, owing to elevated interstitial cell stimulating hormone and testosterone-mimicking effects together with induction of nitric oxide synthase [22]. Yet another study showed that Ashwagandha root extract administration resulted in a significantly greater improvement in spermatogenic activity and increase in serum hormone levels in the oligospermic patients as compared to the placebo treated [23]. This herb evidently combats against oxidative stress by reducing lipid peroxidation as well as protein carbonyl content, increasing sperm count and motility, rejuvenating the seminal plasma levels of antioxidant enzymes.…”
Section: Some Common Ayurvedic Herbs To Improve Male Fertility Ashwagmentioning
confidence: 99%
“…Ashwagandha (Withania somnifera) has been described in the traditional Indian Ayurvedic medicine as an aphrodisiac that can be used to treat male sexual dysfunction and infertility. From the scientific literature it was evident that ashwagandha root extract has increased in sperm concentration, ejaculate volume, and motile sperm count and an increased in the serum levels of testosterone [41]. Cinar et al reported that the supplementation of magnesium (Mg) had increased the both free and total testosterone levels [42].…”
Section: Measurement Of Sex Hormonementioning
confidence: 99%